PENENTUAN POSISI BISNIS PERUSAHAAN FREIGHT FORWARDING DALAM MENGOPTIMALKAN PENGGUNAAN GUDANG - Muhamad Riza Affiat; Rasyid Aviandi; Simon Gultom (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The objective of this study is to find out and analyze the company’s internal and external strategic factors in optimizing warehouse usage at PT. Birotika Semesta.  The method used in this study was the SWOT analysis method.  The result of the study shows that by internal and external matrix (IE), PT Birotika Semesta is at the cell / quadrant IV with total internal strategic factors of 3.21 and the total result of external strategic factors of 2.65 that the company is in developing state.  Therefore, the strategy applied in the company is Grow and Build.  Based on the research analysis result from 4-quadrant SWOT matrix, the position of the company is at quadrant I, formed from the intersection of the positive horizontal axis, which is the company’s strength factor at 0.62 and positive vertical axis which is business opportunities at 0.58.  The most suitable strategy is used by the company; S-O (Strength – Opportunities) strategies which is relying on the company’s strengths to maximize all the available business opportunities.